Experimental & translational stroke medicine (BioMed Central, 2009)
"Experimental & Translational Stroke Medicine encompasses all aspects of topics that relate to identifying and solving problems in translational stroke research."
Keywords: cévní mozková příhoda; neurologie; cerebrovaskulární poruchy; kardiologie; Stroke; Cerebrovascular Disorders; angiologie